Latihan Shooting Free Throw Mengunakan Modifikasi Bola - -, Priyanto (Media Ilmu Keolahragaan Indonesia, 2014)
The purpose of this study was to determine the effect of practice shooting free use size 3 basketball , volleyball , and which one is more influential among free throw shooting drills using 3 size basketball and volleyball on the results of free throw shooting. This research method using the experimental method . The study population was by boys basketball extracurricular participants SMP Negeri 3 Unggaran totaling 16 people . The study design was a pre - test and post-test design . The research instrument used was free throw shooting proficiency test . The amount of validity and reliability in this trial are 0.860 and 0.750 with a significant r - table at 5 % is 0.544 . Since r - count is greater than the r - table then the instrument is valid and reliable. The results of the analysis of data obtained by t-test was 2.411 , while the t - table on db = 7 with a significance level of 0.05 was 2.365 ( t-test = 2.411 > t - table = 2.365 ) , so there is significant relationship between exercise free throw shooting using 3 size basketball and volleyball . Control group mean difference test results obtained at 4.75 , while the mean of the experimental group obtained results 4 , so Me > Mk ( 4.75 > 4 ) .